Formative research in the planning of the syllabus by competence from digital technology - Argota-Pérez, Yadira (2023)
The use of digital technology is related to quality in formative research and allows the development of competencies. The objective of the study was to describe the formative research in the planning of the syllabus by competency from digital technology. From the training on the construction of syllabus by competency, the interpretative score of the formative research was analyzed. Three classes of score range were established: I) 12-14; II) 15-17 and III) 18-20, respectively. Analysis of variance was performed between the arithmetic mean of the score intervals. For the first score interval, 57.89% of the university teachers were recorded. The average between intervals was 14.89±0.43 points being low. A significant difference (p = 0.00) was found between the means of the values registered by class intervals. The demonstration of practical skills in the conceptualization of formative research was considered limiting. It was concluded that there were deficiencies in the mastery of formative research from its registration in the planning of the syllabus by competency with the use of digital technologies. Consequently, the structuring of learning processes in the classroom is impeded, in addition to the gamification of learning processes towards efficient educational management systems.